2021
DOI: 10.1080/09712119.2021.1949999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplemental vitamin C and zinc sulfate on productive performance, egg quality traits and blood parameters of laying hens reared under cold stress condition

Abstract: This study was conducted to investigate the effects of dietary supplemental vitamin C and zinc sulfate on performance, egg quality characteristics and blood parameters of laying hens reared under cold stress condition. A total of 144 Lohmann-LSL Lite laying hens (65 weeks old) were allotted to 24 groups. Based on a 2 × 2 factorial arrangement, four corn-soybean-based diets (2750 kcal/kg ME and 14.69% CP) including two levels of vitamin C (0, 240 mg/kg) and two levels of zinc sulfate (0, 40 mg/kg) were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The Zn is figured out in the diet of poultry in two kinds (inorganic and organic). The form of inorganic grade as zinc oxide (ZnO) (Fawaz et al, 2019) or zinc sulfate (ZnSO 4 ) (Rajabi and Torki, 2021) while organic Zn sources like Zn methionine (Zn-Me) and Zn amino acid complex (ZnAA) (Li et al, 2019). When comparing between two forms of Zn will notice organic trace minerals are chemical complexes made by ions of metal linked to organic material which have complex of polysaccharides, amino acids and peptides, or supply biological availability to metal ions also increase solubility and stability (Gayathri and Panda, 2018;Saeed et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Zn is figured out in the diet of poultry in two kinds (inorganic and organic). The form of inorganic grade as zinc oxide (ZnO) (Fawaz et al, 2019) or zinc sulfate (ZnSO 4 ) (Rajabi and Torki, 2021) while organic Zn sources like Zn methionine (Zn-Me) and Zn amino acid complex (ZnAA) (Li et al, 2019). When comparing between two forms of Zn will notice organic trace minerals are chemical complexes made by ions of metal linked to organic material which have complex of polysaccharides, amino acids and peptides, or supply biological availability to metal ions also increase solubility and stability (Gayathri and Panda, 2018;Saeed et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that zinc supplementation increases eggshell quality since it is an element of the carbonic anhydrase enzyme, supplying carbonate ions during eggshell formation (Ogbuewu & Mbajiorgu, 2022). Moreover, it has been indicated that the secretion of alkaline phosphatase is decreased under stress conditions, and this enzyme interacts with zinc in bone calcium storage (Rajabi & Torki, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similar diet administered by Khukhodziinai et al (2021) resulted in optimum performance in layers challenged with CS (Sahin and Sahin, 2001). Rajabi and Torki (2021) found that the dietary supplementation of 240 mg/kg vitamin C and zinc improved the egg quality of layers challenged with cold temperature between 13 and 15 • C. Sahin and Sahin (2001) concluded that the depressive effect of CS in chickens can be alleviated by vitamin C and chromium. Inconsistent findings have also been reported on the modulatory roles of vitamin C in chickens subjected to high SD (Jahanian and Mirfendereski, 2015;Shewita et al, 2019).…”
Section: Vitamin Cmentioning
confidence: 90%